Seismic Facies Analysis for Lithofacies Prediction, Okam Field of Niger Delta, Nigeria - Okpogo, Emele Uduma; Abbey, Chukwuemeka Patrick; Atueyi, Ifeyinwa Obiageli (Iraqi Journal of Science, 2018)
Seismic facies analysis constrained with well log information have been used to predict lithofacies distribution across the Okam Field of Niger Delta. Density and gamma ray logs were cross-plotted and the seismic section was subdivided vertically into different seismic facies. The delineated lithologies, from well logs were correlated with seismic facies signatures using lines of intersection across the wells. Gamma ray and resistivity logs were used to identify the interfaces between the lithofacies and correlated across the field. Structural interpretation was carried out. Time slices were generated and examined at different intervals within the identified reservoirs. Stratigraphic related attribute and envelope were extracted on these time slices. Three seismic facies type (facies A, B and C) were identified based on reflection amplitude, reflection patterns and continuity. Seismic facies A represents the undisturbed sediments in the Uppermost Benin Formation (parallel continuous, moderate to high reflections). Seismic facies B corresponds to the sand-shale pairs of the Agbada Formation which is diagnostic of moderate to high amplitude subparallel-parallel discontinuous reflections. The chaotic seismic facies signature (facies C) beneath this represents the overpressured mobile deformed Akata shales. The time slices show lateral variation in amplitude from high amplitude continuous reflections to low amplitude chaotic reflections from the southwest to northeast direction of the field. The extracted stratigraphic related attribute and envelope show lateral changes in amplitude from the northeast direction depicting increase in shaliness towards the northeast direction. The lateral variation in lithofacies across the field suggest varied and spatial changes in key reservoir parameters such as porosity and permeability that suggest changes in reservoir qualities across the field.